FXa-α2-Macroglobulin Complex Neutralizes Direct Oral Anticoagulants Targeting FXa In Vitro and In Vivo - Jourdi, Georges; Gouin-Thibault, Isabelle; Siguret, Virginie; Gandrille, Sophie; Gaussem, Pascale; Le Bonniec, Bernard (Thrombosis and Haemostasis, 2018)
Increasing number of patients are treated with direct oral anticoagulants (DOAC). An antidote for dabigatran inhibiting thrombin (idarucizumab) is available but no antidote is yet approved for the factor Xa (FXa) inhibitors (xabans). We hypothesized that a complex between Gla-domainless FXa and α2-macroglobulin (GDFXa-α2M) may neutralize the xabans without interfering with normal blood coagulation.Purified α2M was incubated with GDFXa to form GDFXa-α2M. Affinity of apixaban and rivaroxaban for GDFXa-α2M was only slightly decreased compared to FXa. Efficacy and harmlessness of GDFXa-α2M were tested in vitro and in vivo. Stoichiometric excess of GDFXa-α2M neutralized rivaroxaban and apixaban as attested by clot waveform assay and rotational thromboelastometry, whereas GDFXa-α2M alone had no effect on these assays. Efficacy and pro-thrombotic potential of GDFXa-α2M were also assessed in vivo. Half-life of GDFXa-α2M in C57BL6 mice was 4.9 ± 1.1 minutes, but a 0.5 mg/mouse dose resulted in uptake saturation such that 50% persistence was still observed after 170 minutes. Single administration of GDFXa-α2M significantly decreased the rivaroxaban-induced bleeding time (p < 0.001) and blood loss (p < 0.01). GDFXa-α2M did not increase D-dimer or thrombin–antithrombin complex formation, suggesting a lack of pro-thrombotic potential.GDFXa-α2M is therefore an attractive candidate for xaban neutralization neither pro- nor anticoagulant in vitro as well as in vivo.
Keywords: antidote; apixaban; rivaroxaban; oral anticoagulant